Najmuddin Ath Thufi Mashlahah as Legal Reasoning for Judges' Decisions and Its Contribution to the Reform of Indonesian Islamic Family Law - Alamsyah (SMART: Journal of Sharia, Traditon, and Modernity, 2026)
This article explores the concept of Mashlahah Najmuddin Ath Thufi as a legal reasoning for judges' decisions. The concept of Mashlahah Najmuddin Ath Thufi can be a solution for judges in deciding cases in court. The judges are required to build legal reasoning, who do not have strong legal reasoning can produce decisions that are considered Onvoldoende Gemotiveerd, namely decisions that are insufficient judgment. The question to be answered in this article is how is the construction of Mashlahah according to Najmuddin Ath Thufi in the legal reasoning of judges' decisions? What is the contribution of Najmuddin Ath Thufi's Mashlahah to the renewal of Islamic family law in Indonesia? The method of analysis uses qualitative, while the approach is normative. Data sources are obtained from books, law journals, court decisions and dictates. The results show that, Najmuddin ath Thufi's Mashlahah theory bases the constellation of Mashlahah on the superiority of human reason, based on the interpretation of the Prophet's hadith which reads la dharar wala dhirar. Mashlahah Najmuddin Ath Thufi as the basis of Legal Reasoning for judges' decisions focuses on rechtsvinding (law discovery) and creating new laws (rechtsschepping). Judges because of their position (ambtshalve), are not just the mouth or mouthpiece of the law (bouche de la loi), but become translators or givers of meaning (interpreters). Najmuddin ath Thufi's Mashlahah theory contributes to the reform of Islamic family law in Indonesia through court decisions.